COVID-19 and transport in Asia and the Pacific guidance note. (COVID-19 in Asia and the Pacific guidance notes., 2020)
The unprecedented impact of the pandemic has caused enormous changes to the transport landscape in the region. The guidance note also shares Insights on how the transport sector can help deliver greener and more resilient infrastructure as countries around the world plan for recovery and rejuvenation in the post pandemic future. It is one of a series produced by the Asian Development Bank for key sectors and thematic areas.